The Implications of Market Segmentation, Positioning, and Lifestyle on KPOP Merchandise Online Marketing (Case Study on NCT Community) - Tutik Yoganingsih; Dovina Navanty; Indah Rizki Maulia; Franciscus Dwikotjo; Andrian Andrian (Indonesian Journal of Business Analytics, 2023)
This study aims to determine the effect of Market Segmentation, Positioning, and Lifestyle Implications on Merchandise KPOP Online Marketing. This study was conducted on the NCT community. The number of samples determined was 96 respondents, with sampling techniques using Non-Probability Sampling. This study used a descriptive quantitative method, with a validity test analysis method, reliability test, normality test, multicollinearity test, heterocedaticity test, multiple linear regression test, hypothesis test, and coefficient determination test. The analysis tool in this study is SPSS version 25. The results of this study show that market segmentation, positioning, and lifestyle have a positive and significant effect on online marketing of sex-pop merchandise both in part and simultaneously. The coefficient of determination shows a figure of 0.815 which means that the online marketing variable of the sex population is influenced by market segmentation, positoning, and lifestyle variables of 81%.